2021
DOI: 10.48550/arxiv.2110.00414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Flat-Fading Channels via Meta-Learned Closed-Form Linear Filters and Equilibrium Propagation

Abstract: Predicting fading channels is a classical problem with a vast array of applications, including as an enabler of artificial intelligence (AI)-based proactive resource allocation for cellular networks. Under the assumption that the fading channel follows a stationary complex Gaussian process, as for Rayleigh and Rician fading models, the optimal predictor is linear, and it can be directly computed from the Doppler spectrum via standard linear minimum mean squared error (LMMSE) estimation. However, in practice, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In this section, we present experimental results for the prediction of multi-antenna and/or frequency-selective channels. Numerical examples for single-antenna frequency-flat channels for both offline and online learning scenarios can be found in the conference version of this paper [ 45 ]. For all the experiments, we compute the normalized mean squared error (NMSE) , which is averaged over 100 samples for 200 new frames.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we present experimental results for the prediction of multi-antenna and/or frequency-selective channels. Numerical examples for single-antenna frequency-flat channels for both offline and online learning scenarios can be found in the conference version of this paper [ 45 ]. For all the experiments, we compute the normalized mean squared error (NMSE) , which is averaged over 100 samples for 200 new frames.…”
Section: Methodsmentioning
confidence: 99%
“…In the following, we study the impact of (i) the number of antennas , (ii) the number of channel taps W , (iii) the number of training samples , and (iv) the number of previous frames F , for various prediction schemes: (a) conventional learning, (b) transfer learning, and (c) meta-learning, where each scheme is implemented by using either the naïve or the LSTD parametrization. We set , , and for conventional learning [ 9 , 45 ], whereas , , and for transfer and meta-learning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the importance of optimizing the -CVaR rate for applications that focus on the performance of a small fraction of the clients with the worst channel gains, in Fig. 5, we plot the expected -CVaR rate as a function of the fraction with power = 20dB, Rician fading distribution ℎ ∼ CN(2, 1), = 6 layers, and datasets of size = 10 4 , and for rateand power-allocation vectors and optimized based on different metrics: (i) the surrogate empirical -CVaR rate ˜ G ( , ) defined in (36), (ii) the surrogate average rate ˜ G 1 ( , ) defined in (37), and (iii) the surrogate empirical outage rate ˜ G ( , ) = ( , , [⌊ ⌉] ). It is observed that, for most values of ∈ (0, 1], the average achievable rate for the -fraction of clients with the worst channel gains increases significantly if the rate-and power-allocation vectors are optimized to maximize the surrogate empirical -CVaR rate.…”
Section: B Conditional Value At Riskmentioning
confidence: 99%
“…A review of meta-learning with emphasis on applications to communication systems is available in [28]. Representative examples include meta-learning for learning to demodulate [29], [30] or decode [31]; for end-to-end learning of encoder and decoder [32]; for beamforming adaptation [33], [34]; for proactive resource allocation [35], [36]; and for channel estimation [37].…”
Section: Introductionmentioning
confidence: 99%